Open innovation essentials for small and medium enterprises : a guide to help entrepreneurs in adopting the open innovation paradigm in their business - Escoffier, Luca.; La Vopa, Adriano; Speser, Phyllis L.; Satinsky, Daniel (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2016)
Small and medium enterprises (SMEs) have to approach open innovation differently than large companies. Open Innovation Essentials for Small and Medium Enterprises provides the first comprehensive introduction to the practice of open innovation expressly for entrepreneurs and managers of SMEs. The authors provide strategies, techniques, and "tricks of the trade" that enable SMEs to establish and operate open innovation systems that increase their business's profitability and enhance the long-term value of their equity. They explain how SMEs can use open innovation to develop and sell products and services or to acquire, mature, and sell technology and intellectual property rights. Tools such as brokers, auctions, crowdsourcing, technology transfer, and spin-ups are presented in ways that make it easy to use them in your own company. The entire book can be read on an airplane flight or in an evening, making it useful for people already in business and faculty or students seeking supplemental reading material for courses.
1. Introduction -- 2. IP brokerage and IP auctions -- 3. Technology transfer -- 4. The power of "crowdsolving" -- 5. Emergence of the SME as a source of market-ready technologies -- 6. Conclusion -- Index.
Includes bibliographical references and index.
Title from PDF title page (viewed on February 18, 2016).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Entrepreneurship; Technological innovations; Small business -- Management; business acceleration; crowdsourcing; intellectual property (IP); IP auctions; IP brokerage; open innovation; small and medium enterprises (SMEs); spin-up companies; technology transfer; Electronic books